2006
DOI: 10.1097/01.mbc.0000233362.80486.6c
|View full text |Cite
|
Sign up to set email alerts
|

The association between seated immobility and local lower-limb venous coagulability in healthy adult volunteers: a simulation of prolonged travel immobility

Abstract: This is the first study to examine the hypothesis that prolonged sitting is associated with procoagulant changes in the local lower-limb venous system. A comparison was made with upper-limb venous changes. Changes in markers of thrombin generation, fibrinolysis, endothelial perturbation and haemoconcentration were analysed as 10 healthy adult male participants sat for 8 h. The change in foot volume was estimated. Subjective venous thromboembolism assessment was undertaken hourly, along with 2-week and 4-week s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…While immobility is known to be related to PE risk, 15 to the authors’ knowledge, this is the first study to demonstrate an independent association between immobility and D‐dimer positivity. Two prior studies investigated the issue of hypercoagulability during a simulated airplane flight in 10 healthy subjects and one subject who was heterozygous for factor V Leiden and found no association 16,17 . These results are consistent with our finding of no association between recent travel and D‐dimer results.…”
Section: Discussionsupporting
confidence: 91%
“…While immobility is known to be related to PE risk, 15 to the authors’ knowledge, this is the first study to demonstrate an independent association between immobility and D‐dimer positivity. Two prior studies investigated the issue of hypercoagulability during a simulated airplane flight in 10 healthy subjects and one subject who was heterozygous for factor V Leiden and found no association 16,17 . These results are consistent with our finding of no association between recent travel and D‐dimer results.…”
Section: Discussionsupporting
confidence: 91%
“…Ansari et al . observed a 22% decrease in F 1 + 2 after an 8‐h sitting period but no change in TAT values. An explanation for these findings is that muscle movement during normal daily activities may lead to a constant level of minute coagulation activation; this is illustrated by studies that showed increased thrombin generation after increased muscle use (i.e., exercise) .…”
Section: Discussionmentioning
confidence: 86%
“…This finding is supported by a study by Stricker et al [17], who found no difference in D-dimer but reported an 18% decrease in F 1 + 2 after 6 h of prolonged cramped sitting (which even countered the circadian rhythm). Ansari et al [18] observed a 22% decrease in F 1 + 2 after an 8-h sitting period but no change in TAT values. An explanation for these findings is that muscle movement during normal daily activities may lead to a constant level of minute coagulation activation; this is illustrated by studies that showed increased thrombin generation after increased muscle use (i.e., exercise) [19,20].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies investigated the effect of prolonged immobilization on thrombin generation, but conflicting results were shown [54–67] (Table 4). Stricker et al.…”
Section: Mechanism Of Travel‐related Thrombosismentioning
confidence: 99%